"Home for the Holidays," Poster, 2015 - Salisbury Symphony Orchestra (My University, 2015)
Poster for the December 12, 2015 performance "Home for the Holidays." Featured guest Dominic Armstrong.
Keywords: Music; Salisbury (Md.); Salisbury Symphony Orchestra